Genomic profiling of four cultivated Candidatus Nitrotoga spp. predicts broad metabolic potential and environmental distribution. Issue 12 (December 2018) - Boddicker, Andrew; Mosier, Annika
Abstract Nitrite-oxidizing bacteria (NOB) play a critical role in the mitigation of nitrogen pollution by metabolizing nitrite to nitrate, which is removed via assimilation, denitrification, or anammox. Recent studies showed that NOB are phylogenetically and metabolically diverse, yet most of our knowledge of NOB comes from only a few cultured representatives. Using cultivation and genomic sequencing, we identified four putativeCandidatus Nitrotoga NOB species from freshwater sediments and water column samples in Colorado, USA. Genome analyses indicated highly conserved 16S rRNA gene sequences, but broad metabolic potential including genes for nitrogen, sulfur, hydrogen, and organic carbon metabolism. Genomic predictions suggested thatCa . Nitrotoga can metabolize in low oxygen or anoxic conditions, which may support an expanded environmental niche forCa . Nitrotoga similar to other NOB. An array of antibiotic and metal resistance genes likely allowsCa . Nitrotoga to withstand environmental pressures in impacted systems. Phylogenetic analyses highlighted a deeply divergent nitrite oxidoreductase alpha subunit (NxrA), suggesting a novel evolutionary trajectory forCa . Nitrotoga separate from any other NOB and further revealing the complex evolutionary history of nitrite oxidation in the bacterial domain.Ca . Nitrotoga-like 16S rRNA gene sequences were prevalent in globally distributed environments over a range of reported temperatures. This work considerably expands our knowledge of theCa . Nitrotoga genus and suggests that their contribution to nitrogen cycling should be considered alongside other NOB in wide variety of habitats.